Dosimetric characteristics of the novel 2D ionization chamber array OCTAVIUS Detector 1500. Issue 4 (13th March 2015) - Stelljes, T. S.; Harmeyer, A.; Reuter, J.; Looe, H. K.; Chofor, N.; Harder, D.; Poppe, B.
Abstract : Purpose: The dosimetric properties of the OCTAVIUS Detector 1500 (OD1500) ionization chamber array (PTW‐Freiburg, Freiburg, Germany) have been investigated. A comparative study was carried out with the OCTAVIUS Detector 729 and OCTAVIUS Detector 1000 SRS arrays. Methods: The OD1500 array is an air vented ionization chamber array with 1405 detectors in a 27 × 27 cm 2 measurement area arranged in a checkerboard pattern with a chamber‐to‐chamber distance of 10 mm in each row. A sampling step width of 5 mm can be achieved by merging two measurements shifted by 5 mm, thus fulfilling the Nyquist theorem for intensity modulated dose distributions. The stability, linearity, and dose per pulse dependence were investigated using a Semiflex 31013 chamber (PTW‐Freiburg, Freiburg, Germany) as a reference detector. The effective depth of measurement was determined by measuring TPR curves with the array and a Roos chamber type 31004 (PTW‐Freiburg, Freiburg, Germany). Comparative output factor measurements were performed with the array, the Semiflex 31010 ionization chamber and the Diode 60012 (both PTW‐Freiburg, Freiburg, Germany). The energy dependence of the OD1500 was measured by comparing the array's readings to those of a Semiflex 31010 ionization chamber for varying mean photon energies at the depth of measurement, applying to the Semiflex chamber readings the correction factor k NR for nonreference conditions. The Gaussian lateral dose response function of a single array detector was determined by searching the convolution kernel suitable to convert the slit beam profiles measured with a Diode 60012 into those measured with the array's central chamber. An intensity modulated dose distribution measured with the array was verified by comparing a OD1500 measurement to TPS calculations and film measurements. Results: The stability and interchamber sensitivity variation of the OD1500 array were within ±0.2% and ±0.58%, respectively. Dose linearity was within 1% over the range from 5 to 1000 MU. The effective point of measurement of the OD1500 for dose measurements in RW3 phantoms was determined to be (8.7 ± 0.2) mm below its front surface. Output factors showed deviations below 1% for field sizes exceeding 4 × 4 cm 2 . The dose per pulse dependence was smaller than 0.4% for doses per pulse from 0.2 to 1 mGy. The energy dependence of the array did not exceed ±0.9%. The parameter σ of the Gaussian lateral dose response function was determined as σ 6MV = (2.07 ± 0.02) mm for 6 MV and σ 15MV = (2.09 ± 0.02) mm for 15 MV. An IMRT verification showed passing rates well above 90% for a local 3 mm/3% criterion. Conclusions: The OD1500 array's dosimetric properties showed the applicability of the array for clinical dosimetry with the possibility to increase the spatial sampling frequency and the coverage of a dose distribution with the sensitive areas of ionization chambers by merging two measurements.